The effect of fabrication techniques of temporary crowns on the gingiva health - Eri H. Jubhari; Edy Machmud; Hasminar Hasminar; Armawati Arafi; Catarina A. Kristianti; Sitti Arpa; Maqfirah Amiruddin (Journal of Dentomaxillofacial Science, 2019)
Objective: To determine the effect of manufacturing technique of temporary imitative crown on the gingiva health.Material and Methods: The clinical experimental study was conducted on 10 samples for each the manufacturing technique of temporary imitative crowns. On sample we conduct clinical examination by using plaque and gingival indexes, as well as DHE and scaling at the beginning of the study. And then we count the number of bacterial colonies by using swab method on the cervical part of the provisory. Data were analyzed by chi-square test.Results: There was an effect between the manufacturing technique of temporary imitative crown with plaque and gingival indexes and there was a significant correlation between the manufacturing techniques of provisory on the gingiva health (p<0.05).Conclusion: There was an effect between the manufacturing techniques of the temporary imitative crown on the gingival health. The manufacturing technique of indirect-direct has minimum effect on the gingival health.